MO946THE LEVEL OF POST-TRAUMATIC GROWTH IN KIDNEY TRANSPLANT RECIPIENTS WITH LONG TERM DURATION OF GRAFT. (29th May 2021) - Battaglia, Yuri; Zerbinati, Luigi; Provenzano, Michele; Esposito, Pasquale; Andreucci, Michele; Storari, Alda; Grassi, Luigi
Abstract: Background and Aims: Kidney transplant (KT)can cause a psychological trauma due to changes in self-perception, in interpersonal relationships, and in the philosophy of life. However, the exposure to this traumatic event might lead to not only stress disorders but also positive growth. Primary aim of study was to evaluate the prevalence of post-traumatic growth (PTG)in KTRs. Secondary aim was to explore any association between PTG and psychiatric, psychosocial and medical variables, specifically psychiatric diagnoses, demoralization, as well as physical and general problems or symptoms. Method: KTRs followed up in a single nephrology Unit, were evaluated. Each patient was individually administered MINI International Neuropsychiatric Interview 6.0. and DCPR interview to evaluate ICD-10 psychiatric diagnoses and DCPR diagnoses. PTG Inventory (PTGI), ESAS-revised, CPC, and DS-IT were given as self-report instruments to be filled in. PTGI was used to investigate positive psychological experience of patients after KT on a 0 to 5-point Likert scale(0=I did not experience this change as a result of my KT;5=I experienced this change to a very great degree as a result of my KT).It consists of 21 items divided in five factors: New Possibilities(NP), Relating to Others(RO), Personal Strength(PS), Spiritual Change(SC), and Appreciation of Life(AL).ESAS-revised, DS-IT and CPC were used to examine the severity of physical and psychological symptoms on a 0 to 10 scale; to measure the severity of demoralization on a 0 to 4 scale and to evaluate the physical and general problems in a yes/no(0–1)format, respectively. Results: Data pertaining to 134 out of 143 consecutive outpatients were collected. Clinical characteristics of sample and ranking order of ICD and DCPR diagnoses are shown in Tab.1.Mean score of PTGI total of sample was 52.02 (±20.69).SC(4.26±2.94)experience was markedly lower than RO(16.26±8.18), NP(11.25±5.56), PS(10.91±5.33)and AL(9.77±3.72).PS changes were higher in KTRs with adaption ICD diagnosis(p<0.001);while no SC change was found in KTRs with an ICD diagnosis of mood disorders(p<0.01).DCPR diagnosis of alexithymia and Irritability were associated with low RO score(13.74±6.51 and 13.97±6.95, respectively)(p <0.05).AL subscale was positively correlated with ESAS anxiety symptom and ESAS psychological distress sub-score(p<0.05); and negatively with DS-lT loss of meaning and purpose subscale(p<0.05).Women(57.2±23.07)had higher scores of PTGI than men (49.5±19.04)(p <0.05).No significant correlation was found between CPC problems, blood chemistry and socio-demographic characteristics, including months after transplant. Conclusion: This study shows that KTRs had moderate-to-high levels of PTG which did not change after KT overtime. Also, lower RO score was associated with DCPR diagnosis of alexithymia, highlighting the potential ability of PTGI to identify KTRs who need psychological support. Further multicentre studies should be conducted to investigate the positive psychological changes after KT.